Biocontrol practitioners’ perspectives on emerging genetic-based technologies for weed management - M. A. Rafter; N. Kumaran; D. R. Brookes; M. K. Reid; K. E. Bowers; A. J. McConnachie; M. Cristofaro; R. F. H. Sforza; B. Gooden; M. Hopper (BioControl, 2026)
Weed biocontrol researchers have been at the forefront of developing management solutions for invasive weeds for over 100 years and have a unique perspective to offer on the emerging field of genetic-based technologies such as gene drive and RNAi. As part of the XVI International Symposium on Biological Control of Weeds in May 2023 we conducted a focus group discussion workshop to explore biocontrol practitioners’ perspectives related to: (1) Genetic-based control technologies, and the factors influencing support (or not) for their application to weed management, especially weed biocontrol, (2) perceived opportunities to apply genetic-based control tools to enhance or complement weed biocontrol, focusing on whether/how genetic tools can be applied to fundamentally change the practice of weed biocontrol, and (3) genetic-based control in weed management and how it can operate within the Access and Benefit Sharing regulatory landscape. We analyse the perspectives of biocontrol scientists from the workshop and discuss the prospects and challenges of integrating novel genetic-based control tools with weed biocontrol.

Habitat engineering effects of freshwater mussels in rivers vary across spatial scales - Traci P. DuBose; Caryn C. Vaughn; Garrett W. Hopper; Keith B. Gido; Thomas B. Parr (Hydrobiologia, 2024)

Internal organs and body tissues of free-swimming whale sharks (Rhincodon typus) imaged using underwater ultrasound - M. G. Meekan; F. Thompson; K. Brooks; R. Matsumoto; K. Murakumo; E. Lester; A. Dove; B. Hopper (Frontiers in Marine Science, 2024)
Ultrasound imaging can be used as an effective tool to measure the reproductive status and condition of sharks. This usually requires restraint of the subject, which is not feasible in the wild when the target species is of conservation concern and very large, as is the case for whale sharks. Our study invoked a behavioral response in free-swimming whale sharks that allowed snorkelers to image internal organs and structures using a submersible ultrasound scanner linked to an iPhone in an underwater housing. We were able to reliably locate and monitor the heart and other internal organs inside the body cavity, structures inside the head, and image skin and muscle in the dorsal surface of the sharks. The technique is evaluated as a means for assessing the condition and reproductive status of free-swimming whale sharks.

Central Artery Hemodynamics in Angiotensin II-Induced Hypertension and Effects of Anesthesia - S. E. Hopper; D. Weiss; N. Mikush; B. Jiang; B. Spronck; C. Cavinato; J. D. Humphrey; C. A. Figueroa (Annals of Biomedical Engineering, 2024)

Indirect functional effects of neighbors on food web compartments could not overcome density-dependent limited growth of a grazing minnow - Garrett W. Hopper; Keith B. Gido; Caryn C. Vaughn (Food Webs, 2023)

Little clams with big potential: nutrient release by invasive Corbicula fluminea can exceed co-occurring freshwater mussel (Unionidae) assemblages - Garrett W. Hopper; Jonathan K. Buchanan; Irene Sánchez González; Megan E. Kubala; Jamie R. Bucholz; Matthew B. Lodato; Jeffrey D. Lozier; Carla L. Atkinson (Biological Invasions, 2022)

Nowhere to swim: interspecific responses of prairie stream fishes in isolated pools during severe drought - Garrett W. Hopper; Keith B. Gido; Casey A. Pennock; Skyler C. Hedden; Bryan D. Frenette; Nick Barts; Crosby K. Hedden; Lindsey A. Bruckerhoff (Aquatic Sciences, 2020)

Assessing patient readiness for personalized genomic medicine - Caren J. Frost; Irene L. Andrulis; Saundra S. Buys; John L. Hopper; Esther M. John; Mary Beth Terry; Angela Bradbury; Wendy K. Chung; Katherine Colbath; Natalie Quintana; Elizabeth Gamarra; Brian Egleston; et al. (Journal of Community Genetics, 2019)

Biomass distribution of fishes and mussels mediates spatial and temporal heterogeneity in nutrient cycling in streams - Garrett W. Hopper; Keith B. Gido; Caryn C. Vaughn; Thomas B. Parr; Traci G. Popejoy; Carla L. Atkinson; Kiza K. Gates (Oecologia, 2018)

Improved quality of risk-reducing salpingo-oophorectomy in Australasian women at high risk of pelvic serous cancer - Y. C. Lee; M. Bressel; P. Grant; P. Russell; C. Smith; S. Picken; S. Camm; B. E. Kiely; R. L. Milne; S. A. McLachlan; M. Hickey; M. L. Friedlander; et al. (Familial Cancer, 2017)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

A genome-wide association study for colorectal cancer identifies a risk locus in 14q23.1 - Mathieu Lemire; Conghui Qu; Lenora W. M. Loo; Syed H. E. Zaidi; Hansong Wang; Sonja I. Berndt; Stéphane Bézieau; Hermann Brenner; Peter T. Campbell; Andrew T. Chan; Jenny Chang-Claude; Mengmeng Du; et al. (Human Genetics, 2015)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

The Next Direction for Primatology? A Commentary on Setchell (2013) - Lydia M. Hopper; David B. Morgan; Stephen R. Ross (International Journal of Primatology, 2014)

Association analysis of 9,560 prostate cancer cases from the International Consortium of Prostate Cancer Genetics confirms the role of reported prostate cancer associated SNPs for familial disease - Craig C. Teerlink; Stephen N. Thibodeau; Shannon K. McDonnell; Daniel J. Schaid; Antje Rinckleb; Christiane Maier; Walther Vogel; Geraldine Cancel-Tassin; Christophe Egrot; Olivier Cussenot; William D. Foulkes; Graham G. Giles; et al. (Human Genetics, 2014)

HOXB13 is a susceptibility gene for prostate cancer: results from the International Consortium for Prostate Cancer Genetics (ICPCG) - Jianfeng Xu; Ethan M. Lange; Lingyi Lu; Siqun L. Zheng; Zhong Wang; Stephen N. Thibodeau; Lisa A. Cannon-Albright; Craig C. Teerlink; Nicola J. Camp; Anna M. Johnson; Kimberly A. Zuhlke; Janet L. Stanford; et al. (Human Genetics, 2013)

Screening practices of Australian men and women categorized as “at or slightly above average risk” of colorectal cancer - Driss Ait Ouakrim; Trevor Lockett; Alex Boussioutas; Louise Keogh; Louisa B. Flander; Ingrid Winship; Graham G. Giles; John L. Hopper; Mark A. Jenkins (Cancer Causes & Control, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Adequacy of risk-reducing gynaecologic surgery in BRCA1 or BRCA2 mutation carriers and other women at high risk of pelvic serous cancer - B. E. Kiely; M. L. Friedlander; R. L. Milne; L. Stanhope; P. Russell; M. A. Jenkins; P. Weideman; S. A. McLachlan; P. Grant; J. L. Hopper; K. A. Phillips (Familial Cancer, 2011)

Identification of a novel prostate cancer susceptibility variant in the KLK3 gene transcript - Z. Kote-Jarai; A. Amin Al Olama; D. Leongamornlert; M. Tymrakiewicz; E. Saunders; M. Guy; G. G. Giles; G. Severi; M. Southey; J. L. Hopper; K. C. Sit; J. M. Harris; et al. (Human Genetics, 2011)

Mutation deep within an intron of MSH2 causes Lynch syndrome - Mark Clendenning; Daniel D. Buchanan; Michael D. Walsh; Belinda Nagler; Christophe Rosty; Bryony Thompson; Amanda B. Spurdle; John L. Hopper; Mark A. Jenkins; Joanne P. Young (Familial Cancer, 2011)

Determinants of Preferences for Genetic Counselling in Jewish Women - Carmel Apicella; Stuart J. Peacock; Lesley Andrews; Katherine Tucker; Agnes Bankier; Mary B. Daly; John L. Hopper (Familial Cancer, 2006)

Monocrotophos-Induced Mass Mortality of Swainson's Hawks in Argentina, 1995–96 - Michael I. Goldstein; T. E. Lacher; B. Woodbridge; M. J. Bechard; S. B. Canavelli; M. E. Zaccagnini; G. P. Cobb; E. J. Scollon; R. Tribolet; M. J. Hopper (Ecotoxicology, 1999)